2015
DOI: 10.1387/ijdb.150124sf
|View full text |Cite
|
Sign up to set email alerts
|

External ear microRNA expression profiles during mouse development

Abstract: MicroRNAs (miRNAs) comprise a class of approximately 22 nucleotide regulatory noncoding RNAs that play several roles in diverse biological processes. Recent reports suggest that embryonic development in mammals is accompanied by dynamic changes in miRNA expression; however, there is no information regarding the role of miRNAs in the development of the external ear. The aim of this study was to determine the stage-specific expression of miRNAs during mouse external ear development in order to identify potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The functional role of miR-10 family members in wound healing is not entirely clear. Our results, together with previous observations of consistently high expression of miR-10a/b in mouse fetus and adult skin tissues 21,31,32 , suggest that miR-10a/b is a skin specific microRNA. A recent study on diabetic wound healing showed that the down-regulation of miR-10a/b was partially blocked in diabetic wounds as compared to normal skin wounds 21 , which may contribute to the delayed healing of diabetic wounds.…”
Section: Discussionsupporting
confidence: 86%
“…The functional role of miR-10 family members in wound healing is not entirely clear. Our results, together with previous observations of consistently high expression of miR-10a/b in mouse fetus and adult skin tissues 21,31,32 , suggest that miR-10a/b is a skin specific microRNA. A recent study on diabetic wound healing showed that the down-regulation of miR-10a/b was partially blocked in diabetic wounds as compared to normal skin wounds 21 , which may contribute to the delayed healing of diabetic wounds.…”
Section: Discussionsupporting
confidence: 86%
“…This data set results from the first effort to obtain miRNA expression profiling data of external ear development in mammals. This data should prove useful to understand the role of miRNAs in normal external ear development in mammals and might hint over miRNA involvement in the etiology of microtia [4] Data was validated by Whole mount in situ hybridization in a subset of miRNAs whose mRNA targets have been associated with external ear development and present clear differential spatiotemporal expression patterns (mmu-miR-10a, mmu-miR-200c and mmu-miR-205) [1] , [2] , [3] , [5] . The microarray data presented in this work has been deposited in Gene Expression Omnibus through GEO Series with accession number GSE64945.…”
Section: Discussionmentioning
confidence: 99%
“…Differentially expressed genes (DEGs) between neurons and BMSCs were identified by one-way between-subjects analysis of variance based on Transcriptome Analysis Console software (Torres et al, 2015). Genes with fold-changes |log 2 |>4 were selected as DEGs, and P of <0.05 and false discovery rate (FDR) of <0.05 were used as thresholds.…”
Section: Screening Of Differentially Expressed Genes and Hierarchicalmentioning
confidence: 99%